If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4y + x + 13 = 0 Reorder the terms: 13 + x + 4y = 0 Solving 13 + x + 4y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-13' to each side of the equation. 13 + x + -13 + 4y = 0 + -13 Reorder the terms: 13 + -13 + x + 4y = 0 + -13 Combine like terms: 13 + -13 = 0 0 + x + 4y = 0 + -13 x + 4y = 0 + -13 Combine like terms: 0 + -13 = -13 x + 4y = -13 Add '-4y' to each side of the equation. x + 4y + -4y = -13 + -4y Combine like terms: 4y + -4y = 0 x + 0 = -13 + -4y x = -13 + -4y Simplifying x = -13 + -4y
| -2(h-3)=-h+3(h+6) | | 4x-4=11x-42 | | X^2+11= | | 32*49= | | 7*56= | | 7(x+2)=7(x+6) | | 5x^2-7x=-2 | | 3x^2+3x-5=0 | | 2x+12=10-3x | | 2x+12=10-3 | | (2xy^3)(3x^3y^2)= | | 3(3c+1)=21 | | P+9p=20 | | 3x^3+18x^2+3x+18= | | -8a+2=-2(a+5) | | -5x+4y=-24 | | 2x^3(8x^2-5x+2)= | | 3+7x=6x-15 | | 36*25= | | 5*45= | | 10+5x=6x+22 | | 6*42= | | 3x+10=-3x+58 | | 2(x-3)=3x+7 | | x-9=2x+1 | | -6x-3=2x-75 | | x+10x+21= | | 2x^3+4x^2-30x=0 | | 4-x=-4x-17 | | 3xy+9x= | | 7x+5=6x-3 | | 2+2=98 |